Talk to an Expert: a pilot study on Human Library, University of Colombo - Adhikari, H.I.S.M.; Manatunga, P.K.S.; Silva, M.A.L. (My University, 2016)
A Human Library is a concept that creates a discussion and understanding between people. It operates similar to a traditional library where users can search and read books on a range of disciplines. The difference between a traditional and a human library is that reading is a conversation between the reader and the book. The reader has the opportunity to challenge the prejudices and discrimination. Even though the university system is encouraging interactive learning, the interaction between academics and students are not up to the satisfactory level. The aim of the present study is to introduce the Human Library concept to enhance the interactivity between subject experts and students. The concept of Human Library originated in Denmark in 2000, and since then, has been organized in over 25 countries, this is the first time it is organized in a Sri Lankan university library. In order to achieve the above objective the Library conducted a Human Library as a pilot study during the innovative orientation programme offered for the new entrants to the Faculty of Arts, University of Colombo in 2016.The event was a collaborative initiative of the Faculty of Arts and the Main Library of the university and GIZ FLICT (Facilitating initiatives for Social Cohesion and Transformation).Randomlv 15% of the total population(650)was selected as the sample (100). Seventeen human experts in different fields were selected purposively as resource and were classified according to their specialized subject area using Dewey Decimal Classification system. Both card and on-line catalogues were made available for students to select human expertise according to their requirements. Small groups of students (6-10) were allowed to visit the expert in an assigned seating area and the expert talked to them on the topic and answered the questions. The maximum time allocated for each group was about l5- 20 minutes and a new group was assigned consequently. In this manner the students got the opportunity to talk to several experts during the session. Users as well as the experts were requested to provide their feedback and suggestions at the end of the event. Quantitatively and qualitatively data analysis methods were used to interpret data.51.62% of the sample were .Highly satisfied, with the new experience and interaction they encounter at the human library and 48.38% were satisfied. All the respondents were positive with the new intervention. 8.2% requested to conduct the Human library on other subject specific domains. Experts were very satisfied with the new experience they encountered and showed their willingness to participate for such endeavor in the future. The Human Library which was conducted at the first time in an academic Library in Sri Lanka as a pilot study was a success. The study recommends to incorporate the novel concept of Human Library for other faculties in order to enhance the interaction between academics and students.
Keywords: Human Library, expert interaction, Academic Library